A new genus of Zaeucoilini (Hymenoptera, Cynipoidea, Figitidae, Eucoilinae) from Neotropical Region - Gallardo, Fabiana Edith (2010)
Paradettmeria gen. nov., is described to accommodate Tropideucoila clavicornis. The type specimens studied of Tropideucoila clavicornis and T. weldi show no morphological differences between them, thus, we establish their synonymy, with P. clavicornis the senior name.